E74-like factor inhibition induces reacquisition of hormone sensitiveness decreasing period circadian protein homolog 1 expression in prostate cancer cells - Kohei Koyama; Kiyoshi Takahara; Teruo Inamoto; Naokazu Ibuki; Koichiro Minami; Hirofumi Uehara; Kazumasa Komura; Takeshi Nishida; Takeshi Sakamoto; Hajime Hirano; Hayahito Nomi; Satoshi Kiyama; et al. (Prostate International, 2015)
Purpose: Initiating as an androgen-dependent adenocarcinoma, prostate cancer (PCa) gradually progresses to a castrate-resistant disease following androgen deprivation therapy with a propensity to metastasize. Methods: In order to resolve the mechanism of castrate-resistant PCa, we performed a cDNA-microarray assay of two PCa cell lines, LNCaP (androgen dependent) and C4-2 (androgen independent). Among them, we focused on a novel Ets transcription factor, E74-like factor 5 (ELF5), the expression level of which was extremely high in C4-2 in comparison with LNCaP both in the microarray analysis and real-time polymerase chain reaction analysis, and investigated the biological role in acquisition of androgen-refractory PCa growth. Results: Western blot analysis and morphological analysis using confocal immunofluorescence microscopy demonstrated that ELF5 was expressed mainly in cytosol both in LNCaP and C4-2. Inhibition of ELF5 expression using ELF5-small interfering RNA in C4-2 induced decreased expression of androgen receptor corepressor, period circadian protein homolog 1, and MTT assay of C4-2 after ELF5 small interfering RNA transfection showed the same cell growth pattern of LNCaP. Conclusions: Our in vitro experiments of cell growth and microarray analysis have demonstrated for the first time that decreased expression of period circadian protein homolog 1 due to ELF5 inhibition may induce the possibility of reacquisition of hormone sensitiveness of PCa cells. We suggest that ELF5 could be a novel potential target for the treatment of hormone-refractory PCa patients.